Toxicity of azadirachtin to larvae and adults of Tribolium castaneum (Herbst) - Khalequzzaman, M; Nahar, Jesmun (University Journal of Zoology, Rajshahi University, 2007)
Key words: Azadirachtin; Azadirachta indica; LC50; Tribolium castaneum; larva; adult; residual exposure Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 47-53